2005
DOI: 10.1007/s11102-005-5111-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Efficacy of Bromocriptine in Macroprolactinomas and Giant prolactinomas in Men

Abstract: We prospectively analyzed presentations and long-term therapeutic responses to bromocriptine (BRC) in 29 newly diagnosed men with macroprolactinomas including 14 patients with 'giant prolactinoma'. Clinical symptoms, prolactin (PRL) levels and tumor size on MRI were measured before BRC and sequentially thereafter. The duration of follow-up were 6 to 96 (30.7 +/- 14.4) months. Pretreatment PRL ranged between 124 and 29200 ng/mL (1698 +/- 857.1) and tumor volume was between 2.81 and 132 cm(3) (21.1 +/- 24.3). Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…When very large prolactinomas extend laterally in the cavernous sinus, they will frequently cause cranial nerve palsies (30,47,48,49). The VI (or abducens) nerve is usually involved first, typically resulting in a binocular horizontal diplopia that worsens with gaze.…”
Section: Presenting Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…When very large prolactinomas extend laterally in the cavernous sinus, they will frequently cause cranial nerve palsies (30,47,48,49). The VI (or abducens) nerve is usually involved first, typically resulting in a binocular horizontal diplopia that worsens with gaze.…”
Section: Presenting Featuresmentioning
confidence: 99%
“…Spontaneous CSF rhinorrhoea may occur but is rather uncommon in untreated giant prolactinomas, being most often induced by surgery or by a too effective medical treatment causing rapid tumour shrinkage (8,47,50). In a review of existing literature, Lam et al (51) recently reported 52 patients with non-surgically induced CSF leaks in the setting of a pituitary adenoma.…”
Section: Presenting Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical treatment with dopamine agonists (DA) corrects hyperprolactinemia, decreases tumor size, and restores gonadal function in most patients (1). However, 30-50% of male patients with prolactinomas under DA treatment, both with normal and with high prolactin levels, still remain hypogonadal (2)(3)(4)(5)(6)(7). Persistent hypogonadism in these patients is treated with testosterone replacement, most often with intramuscular injections that require frequent applications and induce large fluctuations in serum testosterone levels with corresponding fluctuations in patients' energy, libido, sexual performance, and mood (8,9).…”
Section: Introductionmentioning
confidence: 99%